Etika dan Moral dalam Pandangan Hadis Nabi Saw - Kholish, Muhammad Jauhar (Jurnal Riset Agama, 2022)
The purpose of this study is to discuss morality in hadith research. This research method uses qualitative research through literature study with content analysis. The results and discussion of this study include general views on morality, hadith about morality, and the meaning of morality according to hadith. The conclusion of this study is that every human being, especially a Muslim, must have good morals following the morals of the Prophet Muhammad S.A.W with the aim that we have noble character. This study recommends the importance of applying a moral approach for all Muslims.